Erectile dysfunction in male lymphoma survivors in a Southeast Asian country - Gin Gin Gan; Diana Leh Ching Ng; Yuen Chwan Leong (Singapore Medical Journal, 2022)
Introduction: Although erectile dysfunction (ED) is one of known long-term complications among male lymphoma survivors, it is not commonly reported, particularly in Southeast Asia. This study aimed to determine the prevalence of ED in lymphoma survivors in Malaysia and its association with anxiety and depression, and effects on quality of life. Methods: This was a cross-sectional study conducted at a tertiary hospital in Malaysia. Patients were all male lymphoma survivors. The self-administered International Index of Erectile Function questionnaire was used to screen for ED. The Hospital Anxiety and Depression Score questionnaire was used to assess for anxiety and depression, and quality of life was assessed using the European Organization for Research and Treatment of Cancer quality of life questionnaire. Results: Overall, 106 patients were recruited. Mean age was 55.7 years, with 61.3% of patients aged above 50 years. Only 67.0% of patients were sexually active and 81.7% of these reported the presence of ED, with only 4.2% having severe ED. Prevalence of ED among younger patients (age ≤50 years old) was 64.5%.The most common reason given by patients who were not sexually active was fatigue. Age was the only factor found to be associated with ED (p <0.005) and severity of ED increased with age. There was no association between ED and psychological stress or quality of life. Conclusion: Prevalence of ED and absence of sexual activity in lymphoma survivors was high. This should serve as a reminder to the treating clinician to offer early treatment and counselling.